Desain Cover Majalah Cosmogirl Indonesia - Regatta Putri Thalia; Elda Franzia (Universitas Trisakti, 2018)
Abstract Cosmogirl Indonesia Magazine Cover Design. Lifestyle becomes aspect that can not be separated from teen girls that keep developing and growing dynamically as nowadays world development. Mostly teen girls use the concept of lifestyle in order to describe their actions. This is the reason why magazine as one of the means of media give information about lifestyle. Cosmogirl Indonesia is one of that kind of magazine that bring the information to teen girls about lifestyle. This research aims to find outthe semiotic meaning of Cosmogirl Indonesia magazine covers in order to inform about teen girls lifestyle. Analyzing data used in this research is semiotic model by Roland Barthes. The object of this research is magazine cover of Cosmogirl Indonesia 2015- 2017. The analyzed data are the communicative symbols which support the development of meaning in those magazine covers to find the denotation and connotation meaningfrom the both relation.AbstrakDesain Cover Majalah Cosmogirl Indonesia. Gaya hidup merupakan sesuatu yang tak terpisahkan dari dunia remaja yang terus berkembang dan bergerak dinamis seiring perkembangan zaman saat ini. Remaja kebanyakan menggunakan gagasan tentang gaya hidup untuk menggambarkan tindakannya sendiri. Inilah alasan mengapa media dalam hal ini majalah yang mempunyai segmentasi remaja perempuan merasa perlu untuk memberikan informasi soal gaya hidup. Majalah Cosmogirl Indonesia merupakan salah satu majalah yang membawa informasi soal gaya hidup di tengah remaja perempuan.Tujuan dari penelitian ini adalah untuk mengetahui makna-makna apa yang terkandung pada cover majalah Cosmogirl Indonesia dalam menginformasikan mengenai gaya hidup remaja perempuan. Analisis data yang digunakan dalam penelitian ini menggunakan model analisis semiotik Roland Barthes. Objek penelitian dalam penelitian ini adalahCover Majalah Cosmogirl Indonesia Tahun 2015-2017 yang membahas lambanglambang komunikasi yang mendukung terbentuknya makna sampul majalah tersebut, sehingga akan diperoleh makna denotasi dan konotasi dari hubungan keduanya.